Packet collision analysis when heterogeneous unlicensed IoT technologies coexist. Issue 6 (1st November 2018) - Ferré, Guillaume; Simon, Eric Pierre
Abstract : This study deals with the impact of unlicensed Internet of Things (IoT) network coexistence in terms of packet collision. The classical packet collision studies based on the Poisson distributed process generally assume homogeneous networks with packets of equal lengths. The authors propose a new approach which can be applied to a more general context including heterogeneous networks and different packet lengths. The proposed approach is based on modelling the vulnerable period and the packet length as uniform random variables. Then, the two main IoT networks considered in unlicensed spectrum, LoRa and Sigfox, are being investigated in more detail. For these two networks, closed‐form analytical formulas for the intra‐and inter‐network probability of packet collisions between nodes are provided and confirmed by simulations results. For this context, it is also shown that the ultra‐narrow band feature of Sigfox is rather a drawback than an advantage from the collision point of view. To enhance the probability of collision, some possible evolutions of the Sigfox physical layer are finally suggested.